Role of CT in evaluating upper aerodigestive tract injuries (Faculty of Medicine Universitas Indonesia, 2006)
This study was aimed to assess the role of CT in upper aerodigestive tract injuries. Twenty six patients presenting with upper aerodigestive tract injury were examined by CT. Nineteen patients had blunt trauma to the neck while seven had penetrating injury. Most of the patients presented soon after injury. Symptoms included respiratory distress (14), neck tenderness (18), hoarseness (7), haemoptysis (2) and odynophagia (3). Soft tissue injuries were seen in 8 patients, aryepiglottic fold edema in 4, aryepiglottic fold haematoma in 1, vocal cord edema in 2 and pyriform sinus obliteration in 5 patients. Supraglottic injuries were seen in six patients, glottic injury in 8 patients and subglottic injuries in 4 patients. Tracheal injuries were seen in 8 patients and included cricotracheal separation (1), tracheal tears (5) and tracheal narrowing (4). Hypopharyngoesophageal injuries were seen in 2 patients. CT was helpful for localization of foreign bodies in 2 cases. CT is useful in deciding management of patients with upper aerodigestive tract injuries obviating the need of open exploration in patients with minimal mucosal injuries, undisplaced fracture and sealed tears. It is particularly helpful in cases when indirect laryngoscopy was not possible. (Med J Indones 2006; 15:81-9)